Templates as heuristics for proving properties of medical devices - Campos, José C. (2015)
This paper briefly describes how property templates have been used to analyse and explore the interactive behaviour of a specific medical device (an IV infusion pump). It is proposed that interactive devices that satisfy properties based on the templates are easier and safer to use. The property templates act as heuristics for the development of suitable properties tailored to the details of the particular device. A mathematically based approach is used to prove that a specification of the device satisfies the properties.